Letter - Schevenels, Walther, b. 1894
030-0200-001 INTERNATIONAL FEDERATION OF TRADE UNIONS 9, Avenue d'Orsay, Paris-VIIe IFTU TELEGRAMS: INTERFED—PARIS TELEPHONE: INVALIDES 45-88 AFFILIATED COUNTRIES: ARGENTINE AUSTRIA BELGIUM CANADA CZECHOSLOVAKIA DANTZIG DENMARK DUTCH EAST INDIES ESTONIA FINLAND FRANCE GREAT BRITAIN GREECE HOLLAND HUNGARY INDIA LUXEMBURG MEMEL TERRITORY PALESTINE POLAND ROUMANIA SOUTH AFRICA SOUTH-WEST AFRICA SPAIN SWEDEN SWITZERLAND YUGOSLAVIA EXECUTIVE COMMITTEE: President W. M. Citrine, Great Britain; Vice-Presidents: H. Jacobsen, Denmark; L. Jouhaux, France; E. Kupers, Holland; Corn. Mertens, Belgium; R. Tayerle, Czechoslovakia; General Secretary: W. Schevenels. Letter F. I. de Sol No. 164 Sch/H 16th February, 1938. Mr. H.V. Tewson, LONDON. Dear Comrade Tewson, I am sorry that, owing to rather a long absence from the office, I am only now able to acknowledge receipt of your two letters of the 1st and 7th February . With reference to your letter of the 1st February, I would like to point out that I did not say that all of the goods distributed in Spain were labelled, but that most of them were. With regard to the proposals you make as to labelling of the goods, I will go into the technical possibilities of this and see what can be done. I am very glad to have Mrs. Adams de Puertas' notes about the relief work in Spain, which are of course of great interest to us, and for which we are much obliged. Yours sincerely, W. Schevenels, General Secretary: 292/946/30/200